Addressing the expectations gap between corporate environmental performance communication and an affected community’s needs : with reference to organisations situated in markman township and the residents of Bluewater Bay, Port Elizabeth - De Villiers, Charl Johannes (University of Pretoria, 2015)
Thesis (PhD)--University of Pretoria, 2014.